B7‐1/B7‐2 blockade overrides the activation of protective CD8 T cells stimulated in the absence of Foxp3+ regulatory T cells. Issue 2 (6th June 2013) - Ertelt, James M.; Buyukbasaran, Esra Z.; Jiang, Tony T.; Rowe, Jared H.; Xin, Lijun; Way, Sing Sing
Abstract : The activation of protective CD8 T cells requires B7‐1/B7‐2 costimulation, even when suppression by Tregs, and in particular, Treg intrinsic CTLA‐4, is circumvented. Abstract : Although T cell activation has been classically described to require distinct, positive stimulation signals that include B7‐1 (CD80) and B7‐2 (CD86) costimulation, overriding suppression signals that avert immune‐mediated host injury are equally important. How these opposing stimulation and suppression signals work together remains incompletely defined. Our recent studies demonstrate that CD8 Teff activation in response to cognate peptide stimulation is actively suppressed by the Foxp3 + subset of CD4 cells, called Tregs. Here, we show that the elimination of Treg suppression does not bypass the requirement for positive B7‐1/B7‐2 costimulation. The expansion, IFN‐γ cytokine production, cytolytic, and protective features of antigen‐specific CD8 T cells stimulated with purified cognate peptide in Treg‐ablated mice were each neutralized effectively by CTLA‐4‐Ig that blocks B7‐1/B7‐2. In turn, given the efficiency whereby CTLA‐4‐Ig overrides the effects of Treg ablation, the role of Foxp3 + cell‐intrinsic CTLA‐4 in mitigating CD8 Teff activation was also investigated. With the use of mixed chimera mice that contain CTLA‐4‐deficient Tregs exclusively after the ablation of WT Foxp3 + cells, a critical role for Treg CTLA‐4 in suppressing the expansion, cytokine production, cytotoxicity, and protective features of peptide‐stimulated CD8 T cells is revealed. Thus, the activation of protective CD8 T cells requires positive B7‐1/B7‐2 costimulation even when suppression by Tregs and in particular, Treg‐intrinsic CTLA‐4 is circumvented.